2005
DOI: 10.1111/j.1399-3054.2005.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the plasma membrane to low temperatures

Abstract: The plasma membrane is considered to be the primary site of injury when plant cells are subjected to extracellular freezing. In order for plants or plant cells to acquire freezing tolerance, it is, thus, necessary that the plasma membrane increases its cryostability during freeze-thaw excursion. During cold acclimation both under natural and artificial conditions, there are compositional, structural and functional changes occurring in the plasma membrane, many, if not all, of which ultimately contribute to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
167
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(175 citation statements)
references
References 35 publications
2
167
0
2
Order By: Relevance
“…This may explain their higher cold sensitivity, considering the role of lipid unsaturation in the maintenance of cell membrane stability (Uemura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain their higher cold sensitivity, considering the role of lipid unsaturation in the maintenance of cell membrane stability (Uemura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cold acclimation involves altered gene expression that affects membrane composition and accumulation of compatible solutes (Uemura et al, 2006). This is possible through the action of specific enzymes which are capable of altering the level of lipidic unsaturation of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Cell Organization and Membranes are Remodeled after Cold Acclimation-The increased vesicularization of the C. reinhardtii cells observed during cold stress exposure can be an indicator of progressive membrane damage, since cell vascularization has been reported as reporter under other stress situations (87). Furthermore the rigidification of the membranes has been proposed as one of the first steps in cold stress signaling in Arabidopsis thaliana (5).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this notion it was previously shown that dramatic molecular and cellular rearrangements occur in response to low temperature stress or pathogen attack. In the case of cold stress, the cell membrane undergoes a series of changes in both lipid and protein composition such that the rigidity of the plasma membrane is elevated (Uemura et al 2006). Changes in cell wall structures were also observed during plant cell cold acclimation (Weiser et al 1990;Yamada et al 2002;Wei et al 2006).…”
Section: Introductionmentioning
confidence: 99%